Antitumor activity of Kielmeyera coriacea leaf constituents in experimental melanoma, tested in vitro and in vivo in syngeneic mice - Figueiredo, Carlos Rogério de; Matsuo, Alisson Leonardo; Massaoka, Mariana Hiromi; Girola, Natália; Azevedo, Ricardo Alexandre; Rabaça, Aline Nogueira; Farias, Camyla Fernandes; Pereira, Felipe Valença; Matias, Natália Silva [UNESP]; Silva, Luciana Pereira [UNESP]; Rodrigues, Elaine Guadelupe; Lago, João Henrique Guilardi; et al. (My University, 2014)
Purpose: The antitumor activity of Kielmeyera coriacea (Clusiaceae), a medicinal plant used in the treatment of parasitic, as well as fungal and bacterial infections by the Brazilian Cerrado population, was investigated. Methods: A chloroform extract (CE) of K. coriacea was tested in the murine melanoma cell line (B16F10-Nex2) and a panel of human tumor cell lines. Tumor cell migration was determined by the wound-healing assay and the in vivo antitumor activity of CE was investigated in a melanoma cell metastatic model. 1H NMR and GC/MS were used to determine CE chemical composition. Results: We found that CE exhibited strong cytotoxic activity against murine melanoma cells and a panel of human tumor cell lines in vitro. CE also inhibited growth of B16F10- Nex2 cells at sub lethal concentrations, inducing cell cycle arrest at S phase, and inhibition of tumor cell migration. Most importantly, administration of CE significantly reduced the number of melanoma metastatic nodules in vivo. Chemical analysis of CE indicated the presence of the long chain fatty compounds, 1-eicosanol, 1-docosanol, and 2-nonadecanone as main constituents. Conclusion: These results indicate that K. coriacea is a promising medicinal plant in cancer therapy exhibiting antitumor activity both in vitro and in vivo against different tumor cell lines.
Keywords: Anti-tumor; Cancer; Cell cycle arrest; Cell migration; Cerrado; Cytotoxic